Peranan Sahsiah dan Kerohanian bagi Mengatasi Masalah Penagihan Dadah - Syed Hadzrullathfi, Syed Omar; Nurul Hanis Nadhirah, Muhammad (2017)
The problem of drug addiction is the most complex global issues faced by the country. Various approaches have been used to prevent and recovery to solve the problem of drug addiction, among which is the approach often discussed religion and Islam. In addressing the issue of drug addiction role of religion is very important to prove that Islam can and can solve many problems. This article discusses the steps or procedures to deal with the drug problem by looking at the religious perspective as an alternative that can enhance the spiritual heir to generation. These elements serve as a fort very personality who can prevent the person from being involved in the drug problem. This study is a qualitative design using document analysis by examining aspects of addiction prevention measures for wisdom. The study found that there are steps that can be used for the wisdom of drug addicts, namely bi al-Hal, entertainment or Islamic spirituality, psychology, social development, personal development and spirituality. Therefore, sympathize and community groups this approach is the core and the wisdom of those addicted to drugs.